BURUNG JUNAI MAS (CALOEANAS NICOBARICA) SUMBER DAYA ALAM LOKAL DI HALMAHERA TENGAH - Kamil Jumat (LEMBAGA PENELITIAN PUBLIKASI DAN PENGABDIAN KEPADA MASYARAKAT UNIVERSITAS MUHAMMADIYAH MALUKU UTARA, 2019)
Jiew Island is a small island located on the edge of the Pacific Ocean on the east side of Halmahera Island. The island is bordered directly by the Republic of Palau and administratively is in the administrative area of Central Halmahera Regency. In addition to the outer islands, Jiew Island bio-ecologically has unique natural resources both flora and fauna. In addition to the flora and fauna on this island there are also various types of marine life that until now have not been identified both types and numbers. The purpose of this study is to examine the presence of the Junai Mas or by its scientific name Caloenas nicobarica as one of the local natural resources of the community through the initial study of the characteristics of Junai Mas on the island of Jiew. The anatomy of this bird is of medium size, with a length of about 34 cm, from one of the genus Caligeas dove, has grayish black feathers coated with golden green, shiny on the neck, coat, back and wings. Elongated neck and wing feathers. The beak is black with a slight bump on the base. Adult birds have short white tails, gray legs with yellow claws. Blackish-colored young birds with short neck feathers and brownish legs.